Improvement of in vitro dissolution profile of poorly aqueous soluble anti-parasitic agent ivermectin using novel hydrophilic polymeric carriers - Rahman, Tanvir; Abdurrahim, Md; Afrin Rintu, Koma; Sarkar, Md Raihan; Kabir, Md Alamgir; Islam, Dipa; Hasanuzzaman, Md (Bangladesh Journal of Scientific and Industrial Research, 2023)
Ivermectin (IVM), a BCS Class II drug with weak water solubility, has minimal oral absorption and dissolution. This study aims to enhance the dissolution profile of IVM by performing solid dispersion methods using four hydrophilic polymers: Kollicoat IR, Kollidon 90F, poloxamer 407, and hydroxypropyl methylcellulose (HPMC). The solid dispersion formulations (SDF) were made through physical mixing, solvent evaporation, and melt solvent/fusion. Using three ratios of IVM and hydrophilic carriers (1:1, 1:2, and 1:3), the cumulative release rate of IVM from formulations formed by physical mixing, solvent evaporation, and fusing was much larger than pure IVM (10%). IVM release rates from formulations including Poloxamer 407, Kollicoat IR, and HPMC polymers were 76% (fusion technique), 69% (physical mixing), and 47% (solvent evaporation method). The research demonstrated that fusion optimized drug solubility better than physical mixing and solvent evaporation. The research found that SD of weakly water-soluble IVM with Kollicoat IR/Poloxamer 407 improves its in vitro dissolving profile much better. Bangladesh J. Sci. Ind. Res. 58(4), 209-220, 2023